Prospective, Split-Face, Randomized, Long-Term Blinded Objective Comparison of the Performance and Tolerability of Two New Hyaluronic Acid Fillers. Issue 12 (December 2017) - Trevidic, Patrick; Andre, Pierre; Benadiba, Laurent; Deutsch, Jean-Jacques; Galatoire, Olivier; Garcia, Philippe; Grand-Vincent, Anne; Boisnic, Sylvie; Kerihuel, Jean-Charles; Salomon, Catherine
Abstract : BACKGROUND: There are requirements for long-term, objective comparisons of hyaluronic acid (HA) dermal fillers. OBJECTIVE: To compare efficacy and tolerability of ART FILLER Universal (AFU) and ART FILLER Fine lines (AFFL) with the existing HA fillers for the treatment of nasolabial folds and crow's feet. MATERIALS AND METHODS: Prospective, randomized, rater- and patient-blind, split-face comparison of AFU with JUVEDERM Ultra 3 (JUV) and AFFL with FIRST LINES PureSense (FLPS). The severity of nasolabial folds and crow's feet was assessed by independent blinded evaluators using the Lemperle scale at baseline, day (D) 30/D45, D90, and D180. Tolerability, Global Aesthetic Improvement Scale (GAIS), wrinkle volumes, and skin thickness and density were also measured at D30/D45, D90, and D180. RESULTS: At D30 and D180 respectively, 61 and 67 patients were assessed. Scores for nasolabial folds and crow's feet showed statistically significant improvements at D30, D90, and D180. AFU and AFFL were noninferior to JUV and FLPS, respectively. Most patients showed GAIS improvements, maintained until at least D180 and significant increases of collagen synthesis in crow's feet and nasolabial folds. Treatments were well tolerated. CONCLUSION: AFU and AFFL are noninferior to comparators. The methodology used represents a novel approach to augment existing clinical assessment of HA fillers.